The "Celebrated Indian Herb Doctor":: Francis Tumblety in Saint John, 1860 - Twohig, Peter (Acadiensis, 2010)
Abstract Francis Tumblety, the "Celebrated Indian Herb Doctor," arrived in Saint John in the summer of 1860. He quickly became embroiled in conflict with the established medical community and even stood accused of manslaughter. This article examines Tumblety’s brief stay in Saint John as a way of illustrating the contested nature of medical practice in the mid-19th century. Understanding the career of such a practitioner provides insight into the range of therapeutic choices that were available during these years and into the struggle of orthodox medicine to limit these choices.